SYNTHESIS OF A STATIC DETERMINED HINGED SPATIAL MECHANISM OF A TUMBLING MACHINE - ZALYUBOVSKYI, MARK; PANASYUK, IGOR; KOSHEL, SERHIY; KOSHEL, OLEXANDR; ROMANIUK, OKSANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
One of the possible options for freeing the spatial mechanism of a tumbling machine for processing parts from passive coupling is proposed. A synthesis of a statically determined spatial mechanism with a double degree of mobility of a machine for processing parts (tumbling machine) has been carried out, where the working capacity performs a complex spatial movement. A design of a tumbling machine has been developed, which contains two driving links - a driving shaft and a crank. The introduction of an additional movable crank link into the kinematic chain of the spatial mechanism of the machine will allow, if necessary, to turn on the effect of additional shaking of the working capacity, which effectively affects the increase in the intensity of movement of the loose working mass. The use of this machine design provides increased reliability during its operation and at the same time contributes to increasing productivity during rolling operations or mixing loose fine-dispersed substances, reducing energy consumption, and may affect the expansion of the scope of use of this type of equipment. A detailed description of the principle of operation of the developed design of the rolling machine has been made. A special drive design has been synthesized, which allows transmitting torque to the drive shaft of the machine, which simultaneously performs additional reciprocating movement, and the principle of its operation is described. The synthesized drive design contains a hinged component and a chain transmission with three sprockets, two of which, in addition to rotational movement, additionally perform reciprocating movement along the guides. During the research, an analytical approach was used to synthesize a hinged statically determined mechanism with rotational and one translational kinematic pair and a special drive design, and the design of a tumbling machine was modeled and developed in the SolidWorks 2021 computer-aided design software.